The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s42506-019-0030-9
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitudes about the use of emergency contraception among college students in Tamil Nadu, India

Abstract: Background: In India, a large number of pregnancies are unplanned resulting in unsafe and illegal abortion. For every legal abortion, 10 to 11 illegal abortions are occurring which endangers the health and survival of the women. In recent years, there is an increase in unwanted and unintended pregnancy at the early age group. Usage of emergency contraception (EC) can decrease the unwanted pregnancy and provide a healthier life. Aim: The aim of study is to assess the knowledge and attitude regarding EC among co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
26
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 24 publications
6
26
1
4
Order By: Relevance
“…Besides Burundi, the prevalence of wasting and underweight was highest in Burkina Faso and Chad. This finding is in line with previous evidence that shows that wasting and underweight are most prevalent in Burkina Faso [ 27 ] and Chad [ 28 ].…”
Section: Discussionsupporting
confidence: 93%
“…Besides Burundi, the prevalence of wasting and underweight was highest in Burkina Faso and Chad. This finding is in line with previous evidence that shows that wasting and underweight are most prevalent in Burkina Faso [ 27 ] and Chad [ 28 ].…”
Section: Discussionsupporting
confidence: 93%
“…This study was conducted to assess skin-to-skin care practice and its associated factors among postnatal mothers who visit Gurage Zone public health centers; we found that 35.3% (95% CI; 31.3%–40.4%) of participants were practiced skin-to-skin care to their newborn. The finding of this study was comparable with the studies conducted in Harar city, eastern Ethiopia 34.4%, 14 Gambia 35.7%, 15 and Brazil 37.5%. 17 The proportion of SSC practice in this study was higher than studies conducted in four regions of Ethiopia 25.8%, 18 Eastern India 15%, 7 and rural Ghana 10%.…”
Section: Discussionsupporting
confidence: 90%
“…This difference was due to the difference in the distribution of health facilities where the distribution of health facilities in the study setting is found in urban areas whereas, in the Gambia, the health facilities are more distributed and found in rural area. 15 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Age as a determinant unintended pregnancy was also found in previous studies 9,14,15 . Age other than related to the unpreparedness of women when they were teenagers 16,17 , also related to the number of children desired and the reproductive ability of women 18 .…”
Section: Discussionmentioning
confidence: 99%